Beda Efek Mirror Therapy dengan Proprioceptive Neuromuscular Facilitation dalam Meningkatakan Fungsional Anggota Gerak Atas pada Pasien Pascastroke di RS Efarina Pangakalan Kerinci - Ginting, Isaharpika Br; Purba, Yeni Trisna; Tarigan, Bunga Shinta Pratiwi (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2024)
Objective: To determine the difference between Mirror Therapy (MT) and Propioceptive Neuromuscular Facilitation (PNF) in increasing the functional ability of the upper limb (AGA) in post-stroke patients. Method: This research is a quasi experiment. Measurement of the functional ability of AGA is measured using the Wolf Motor Function Test (WMFT). The sample consisted of 12 patients at the Jakarta Islamic Hospital. The sample group I consisted of 6 samples with MT intervention and group II consisted of 6 samples with PNF Results: measurements in group I before the intervention had a mean and standard deviation of 31.67± 13.983 and after the intervention it was obtained 33.50 ± 3.834. Whereas in group II the measurement before the intervention obtained a value of 33.33 ± 6.831 and after the intervention 37.83 ± 6.911. The Shapiro Wilk test showed normal distribution data, while Levene's test showed homogeneous variance. Hypothesis I test results with T-Test Related, obtained p <0.0001. In the second hypothesis test with T-Test Related, it was found that p <0.0001. Hypothesis III test with independent sample t-test shows p value <0.0001. Conclusion: There is a different effect between MT and PNF in AGA in post-stroke patients.